Recommendations for further improvement of the deceased organ donation process in Belgium. Issue 5 (2nd September 2016) - Hoste, Pieter; Ferdinande, Patrick; Hoste, Eric; Vanhaecht, Kris; Rogiers, Xavier; Eeckloo, Kristof; Van Deynse, Dominique; Ledoux, Didier; Vandewoude, Koenraad; Vogelaers, Dirk
Abstract : Belgium has achieved high deceased organ donation rates but according to the medical record data in the Donor Action database, deceased potential donors are still missed along the pathway. Between 2010 and 2014, 12.9 ± 3.3% of the potential donors after brain death (DBD) and 24.6 ± 1.8% of the potential donors after circulatory (DCD) death were not identified. Conversion rates of 41.7 ± 2.1% for DBD and 7.9 ± 0.9% for DCD indicate room for further improvement. We identify and discuss different issues in the monitoring of donation activities, practices and outcomes; donor pool; legislation on deceased organ donation; registration; financial reimbursement; educational and training programs; donor detection and practice clinical guidance. The overall aim of this position paper, elaborated by a Belgian expert panel, is to provide recommendations for further improvement of the deceased organ donation process up to organ procurement in Belgium.